Sektor państwowy a sektor prywatny w gospodarce Francji - Przybylska-Kapuścińska, Wiesława (Wydział Prawa i Administracji UAM, 1976)
Private property ceased to by the only form of property in contemporary developed capitalistic countries. It is still playing a dominating rolle in the economy, but a new subject of property appears in addition to it:the state as a collective capitalist. Apart from traditional lines of business firms dealing with industry production and services belang to the state. In relation to it there appears a problem of interrelationships between these two forms of property in individual branches. According to the type of branch the state sector may have one of three positions with regard to the private sector. In such activities as: coal industry, railways, power supply and telecommunication — state enterprises held a monopolistic position. It is connected with high capital intensity of these branches. A compétitive position towards private property is characteristic for the following lines of business: car industry, chemistry, construction, shipbuilding, aircraft and military industries. It results from political, economic and social reasons, as well as from the tradition. There are also branches, in which the state sector plays a secondary role: agriculture, services, trade and others. The private sector — state sector relation seems to be stabilized.
State Sector and Private Sector in Economy of France